2010
DOI: 10.1080/02185371003669270
|View full text |Cite
|
Sign up to set email alerts
|

Eurocentric Social Science and the Chinese Region

Abstract: European social scientists have identified a 'new regionalism' based on the existence of the region as a scale of economic, political and cultural life. This article asks whether these tendencies represent a local European experience, or whether similar movements can be found in China and whether European theorizations speak to the Chinese experience. The article explores the evolution of Chinese provincialism in the twentieth century. It concludes that debates about provincial autonomy both have resonance wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…Im Rahmen der Untersuchung von Othering-Prozessen in Forschungssituationen kann von der generellen Annahme ausgegangen werden, dass transnationale Forschungen in unterschiedlichen kulturellen Kontexten eine Leerstelle hinterlassen: Es ist wenig bekannt über die ›Blackbox‹ transnationaler Forschung zu China, deren Epistemologie sowie die Methodologi-en, die in der jeweiligen Forschung lokal zur Anwendung kommen (Scharping 2000). Während ein Weg zur Überbrückung dieser Leerstelle die eurozentrische Theoriebildung war und bislang ist, haben verschiedene Disziplinen, wie bereits argumentiert, eben jene stillschweigenden Verfahren kritisiert, die Positionen und Theoriebildung aus dem Globalen Norden als die dominierenden in einem Weltsystem postulieren (Bhambra 2009;Connell 2007;Tomaney 2010;Wallerstein 1997;Young 2004). Durch die Reflexion jener epistemologischen ›Blackbox‹ können die damit einhergehenden methodologischen Probleme in konzeptueller wie geopolitischer Hinsicht reflexiv fruchtbar gemacht werden.…”
Section: Othering Im Kontext Sozialwissenschaftlicher Chinaforschungunclassified
See 1 more Smart Citation
“…Im Rahmen der Untersuchung von Othering-Prozessen in Forschungssituationen kann von der generellen Annahme ausgegangen werden, dass transnationale Forschungen in unterschiedlichen kulturellen Kontexten eine Leerstelle hinterlassen: Es ist wenig bekannt über die ›Blackbox‹ transnationaler Forschung zu China, deren Epistemologie sowie die Methodologi-en, die in der jeweiligen Forschung lokal zur Anwendung kommen (Scharping 2000). Während ein Weg zur Überbrückung dieser Leerstelle die eurozentrische Theoriebildung war und bislang ist, haben verschiedene Disziplinen, wie bereits argumentiert, eben jene stillschweigenden Verfahren kritisiert, die Positionen und Theoriebildung aus dem Globalen Norden als die dominierenden in einem Weltsystem postulieren (Bhambra 2009;Connell 2007;Tomaney 2010;Wallerstein 1997;Young 2004). Durch die Reflexion jener epistemologischen ›Blackbox‹ können die damit einhergehenden methodologischen Probleme in konzeptueller wie geopolitischer Hinsicht reflexiv fruchtbar gemacht werden.…”
Section: Othering Im Kontext Sozialwissenschaftlicher Chinaforschungunclassified
“…Durch die Reflexion jener epistemologischen ›Blackbox‹ können die damit einhergehenden methodologischen Probleme in konzeptueller wie geopolitischer Hinsicht reflexiv fruchtbar gemacht werden. Gerade feministische und postkoloniale Ansätze zeigen im Anschluss daran, wie die spezifische Situiertheit und hegemoniale Machtverhältnisse in wissenschaftliche Forschungspraktiken eingebettet sind (Bhambra 2014;Harding 1991;Reuter/Villa 2010), und verdeutlichen, dass wir als Forschende mithin in geopolitische Ungleichheitsverhältnisse verstrickt sind (Mignolo 2012;Tomaney 2010).…”
Section: Othering Im Kontext Sozialwissenschaftlicher Chinaforschungunclassified
“…The studies reported above are drawn mainly from a developed world context. Anthropological studies typically examine local belonging in the context of 'traditional' societies (Lovell, 1998), but there is also a strong case for examining the forms of local belonging in rapidly urbanizing societies of the Global South (see Tomaney, 2010b). Devine- Wright (2013) emphasizes the inherently dynamic nature of place attachment and the absence of research on how it changes over time.…”
Section: Agendasmentioning
confidence: 99%
“…I find it also in much 20th-century Irish literature -notably Joyce, Kavanagh and Heaney (see Tomaney, 2010b) -which seeks to reconcile the parish and the universe. In addition, it can be discovered in the 20th-century American poetic tradition that is deeply rooted in place and ecological concerns, which includes the Black Mountain poets, Gary Snyder and beyond them Walt Whitman (Rasula, 2002), although of course it exists in many other cultures (see Tomaney, 2010a, for a treatment of some of these issues in Chinese culture).…”
Section: Attachments and Belongingsmentioning
confidence: 99%